2005
DOI: 10.4049/jimmunol.174.10.6391
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Is Required for a Proper Immune Response to Bacterial and Viral Pathogens in the Female Brain

Abstract: Although the neuroprotective effects of estrogens are well recognized, the exact mechanisms involved in the ability of these sex steroids to protect the cerebral tissue still remain unclear. We tested in our study the hypothesis that estradiol (E2) modulates the innate immune response and expression of genes encoding proteins that a provide survival signal to neurons during infection. Mice received a single systemic or cerebral injection of LPS to trigger a robust but transient inflammatory reaction in the bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
89
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 49 publications
5
89
1
Order By: Relevance
“…In this regard, it should be highlighted that while there is abundant information about gender differences in suicide risk factors and suicidal behavior, to our knowledge, postmortem studies have not reported major neurochemical or gene expression differences between the brain of suicides women and men. The observed sex-differences in cytokine expression in the present study may be of relevance because sex-differences in the immune and cytokine response of the brain have been reported in experimental animal models (46)(47)(48). Therefore, cytokines may further our understanding of neurochemical sex-differences in the brain that may be related to sex-differences in behavior.…”
Section: Discussionmentioning
confidence: 78%
“…In this regard, it should be highlighted that while there is abundant information about gender differences in suicide risk factors and suicidal behavior, to our knowledge, postmortem studies have not reported major neurochemical or gene expression differences between the brain of suicides women and men. The observed sex-differences in cytokine expression in the present study may be of relevance because sex-differences in the immune and cytokine response of the brain have been reported in experimental animal models (46)(47)(48). Therefore, cytokines may further our understanding of neurochemical sex-differences in the brain that may be related to sex-differences in behavior.…”
Section: Discussionmentioning
confidence: 78%
“…In the brain, enhanced immune responses in female with respect to male were reported in mice after i.n. inoculation with vesicular stomatitis virus (Barna et al, 1996), herpes simple virus-2 or intracerebral administration of LPS (Soucy et al, 2005). This has been proposed to be related to a stronger cytokine expression and transfer from innate to adaptive immune responses in females (Soucy et al, 2005) in which TNF-a have been shown to play an important role (Rahman and McFadden, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…inoculation with vesicular stomatitis virus (Barna et al, 1996), herpes simple virus-2 or intracerebral administration of LPS (Soucy et al, 2005). This has been proposed to be related to a stronger cytokine expression and transfer from innate to adaptive immune responses in females (Soucy et al, 2005) in which TNF-a have been shown to play an important role (Rahman and McFadden, 2006). Relevant to this point, it has been recently shown that mice deficient in TNF-a receptors show reduced immobility time in the FST supporting a role for TNF-a in behavioral responses of depression (Simen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies show that ERα may be necessary to mount an effective immune response. For example, ERKO mice do not show the expected increase in the LPS receptor TLR-2, after intracerebral LPS injections (Soucy et al, 2005), suggesting that the general innate immune response may be compromised in the absence of ERα.…”
Section: Discussionmentioning
confidence: 99%